Microbiology : - Black, Jacquelyn G. (John Wiley & Sons, 2005)
Microbiology: Principles and Explorations has been a best-selling textbook for several editions due to the author's engaging writing style where her passion for the subject shines through the narrative. The text's student-friendly approach provides readers with an excellent introduction to the study of Microbiology. This text is appropriate for non-major and mixed major microbiology courses, allied health, agriculture and food sciences courses too